Analysis of the Effect of Sieve Size on the Efficiency and Quality of Milling Results Dried Shrimp - Juanda Purba; Jhon Supriadi Purba; Tambos August Sianturi (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2025)
This study was conducted to investigate the operation of the dried shrimp grinding machine. This study was also undertaken to determine the differences in grinding results using three different sieve sizes. There are three sieve sizes used, namely, 5 mm, 7mm, and 9mm. This study was conducted to determine the results of grinding dried shrimp from fine to coarse, as the demand for ground shrimp in the market varies. Therefore, the researcher conducted this study with the aim of meeting market demand.